Дослідження техніко-економічних показників технологій влаштування реставраційних штукатурок - Молодід, О. С. (Ways to Improve Construction Efficiency, 2013)
The article presents the results of comparison of technical and economic indicators unit of the proposed restoration opus signinum plaster developed technology with manual and mechanized application of plaster Ceresit CR 63. Compared device plaster layer thickness of 30 mm, 100 m2 for the following technical and economic parameters: complexity, wages, duration of the process, material costs for plaster and equipment cost.